Prognostic value of KRAS G12C in advanced non-small cell lung cancer with high PD-L1 expression treated with upfront immunotherapy: a systematic review and meta-analysis (Swiss Medical Weekly, 2024)
AIM: This study aims to evaluate the prognostic role of the KRAS G12C mutation in patients with advanced non-small cell lung cancer and PD-L1 expression ≥50% who are treated with immune checkpoint inhibitor monotherapy.METHODS: We conducted a systematic review of clinical studies fulfilling the following criteria: (1) enrolling patients with advanced/metastatic non-small cell lung cancer with high PD-L1 tumour expression receiving first-line therapy with anti-PD-(L)1 immune checkpoint inhibitors; (2) comparing the outcomes of patients with the KRAS G12C mutation to those without this mutation, and (3) reporting overall survival and progression-free survival (PFS). The electronic databases Medline, EMBASE, Cochrane and Google Scholar, along with reference lists, were systematically searched.RESULTS: We identified four publications that fulfilled the inclusion criteria, comprising a total of 469 patients. Of these, two studies reported hazard ratios (HR) for PFS, resulting in a final pooled patient sample of 163 for the meta-analysis. In patients with non-small cell lung cancer who received anti-PD-(L)1 monotherapy, the presence of a KRAS G12C mutation was associated with improved PFS compared to patients with KRAS wild-type tumours, with a pooled hazard ratio of 0.39 and a 95% Confidence Interval (CI) of 0.25–0.63. Among all patients with KRAS mutations, those harbouring a KRAS G12C mutation had improved PFS compared to patients with any other KRAS mutation (pooled HR 0.33, 95% CI 0.19–0.57).CONCLUSIONS: Patients with non-small cell lung cancer who have the KRAS G12C mutation and high PD-L1 expression demonstrate favourable PFS with first-line PD-(L)1 immune checkpoint inhibitor monotherapy compared to patients with KRASwt or other KRAS mutations and high PD-L1 expression.